Thermal Process Requirement and Storage Stability of Canned Guava Drink - Sulaiman, Ishak (1993)
A thermal process for canned guava drink was evolved on the basis of inactivation of pectinesterase (PE), the most heat resistant enzyme naturally present in guava. The thermostability of PE in guava drink was determined according to the thermal inactivation time tube method. The kinetics of thermal inactivation of PE in guava drink showed it obeyed first-order reactions. The thermal inactivation time curve of the enzyme was analogous to the thermal death time curve of bacteria. As the heat resistance of spoilage microorganisms is lower than PE in acidic conditions, the enzyme was used in the thermal process evaluation of canned guava drink.